Publication David Lamelas : responses to three statements - Arnatt, Keith; Barry, Robert; Brouwn, Stanley; Buren, Daniel; Burgin, Victor; Claura, Michel; Gilbert & George; Lamelas, David; Latham, John; Lippard, Lucy, R.; Maloney, Martin; Reise, Barbara, M.; et al. (London : Nigel Greenwood Inc Ltd, 1970)
Keith Arnatt - Robert Barry - Stanley Brouwn - Daniel Buren - Victor Burgin - Michel Claura - Gilbert & George - John Latham - Lucy R. Lippard - Martin Maloney - Barbara M. Reise - Lawrence Weiner - Ian Wilson
Publication David Lamelas : responses to three statements. Their responses are published in this book, which constitutes the form of the work, presented first in Nigel Greenwood Inc Ltd London, between the 23rd of November and the 6th of December 1970.
boek